Nacionalne ideologije i umjetnost u 19. stoljeću na primjeru fresaka u apsidama đakovačke katedrale - Damjanović, Dragan, povjesničar umjetnosti (Array, 2009)
Sažetak: Based on international experience and the present socioeconomic situation in Croatia three theoretical models were created about influence of work-related stressors and crossover effect on marriage quality. The first model represented the direct influence of work-related stressors on marriage quality and the other two were mediation ones. The first mediation model consisted of four exogenous and four endogenous variables and in the second mediation model covariate variable was added. The models were tested on 340 full-time-employed marital couples representing the quota sample of Zagreb and Zagreb metropolitan area. Models were evaluated using SEM separately for wives and for the husbands. The best model for predicting marital partners' marriage quality was the mediation model with covariate. By this model 39% of husband's and 57% of wife's marriage quality was explained. Also, according to results, there was a crossover effect present, i.e. work-related stressors of one marital partner influenced the marriage quality of the other marital partner